2017
DOI: 10.1111/1759-7714.12518
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent ROS1 gene rearrangement and KRAS mutation in lung adenocarcinoma: A case report and literature review

Abstract: Lung adenocarcinomas with gene rearrangement in the receptor tyrosine kinase ROS1 have emerged as a rare molecular subtype. Although these lung adenocarcinomas respond to ROS1tyrosine kinase inhibitors, many patients ultimately acquire resistance. ROS1gene rearrangement is generally mutually exclusive with other driver genomic alterations, such as those in EGFR, KRAS, or ALK, thus multiple genomic alterations are extremely rare. Herein, we report a case of a 42‐year‐old man diagnosed with lung adenocarcinoma p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…We found that MAPK pathway activation is necessary and sufficient for survival of cells expressing SDC4-ROS1 and SLC34A2-ROS1, suggesting MAPK pathway reactivation may be a mechanism of resistance to crizotinib monotherapy. Consistent with this notion, there are limited reports of RAS-activating mutations or upregulation driving resistance to crizotinib in the setting of ROS1 fusion-driven cancers (49,50). Identification of the downstream pathways activated by an oncogene could be critical to predict what pathway a tumor may reactivate during the evolution of resistance, as we showed in EML4-ALK NSCLC (20).…”
Section: Discussionsupporting
confidence: 59%
“…We found that MAPK pathway activation is necessary and sufficient for survival of cells expressing SDC4-ROS1 and SLC34A2-ROS1, suggesting MAPK pathway reactivation may be a mechanism of resistance to crizotinib monotherapy. Consistent with this notion, there are limited reports of RAS-activating mutations or upregulation driving resistance to crizotinib in the setting of ROS1 fusion-driven cancers (49,50). Identification of the downstream pathways activated by an oncogene could be critical to predict what pathway a tumor may reactivate during the evolution of resistance, as we showed in EML4-ALK NSCLC (20).…”
Section: Discussionsupporting
confidence: 59%
“…In our cohort, two octogenarian males harbored a ROS1 translocation, and both had concurrent clinically relevant mutations ( ROS1 + / KRAS + and ROS1 + / NRAS + ). Similar anecdotal cases of concurrent ROS1 rearrangements and KRAS mutations were recently reported [21,22], whereas no cases of ROS1 translocations and NRAS variants have been described so far. ROS1 gene rearrangements could be targeted by TKIs, but KRAS / NRAS gene point mutations could lead to ineffective inhibition through inactivation of the RAF/MEK/ERK signaling pathway.…”
Section: Discussionsupporting
confidence: 78%
“…RAS-MAPK pathway hyperactivation has an established role in promoting resistance to EGFR, ALK, BRAF, and ROS1 targeted therapies via diverse mechanisms including KRAS amplification and KRAS, BRAF, and NF1 mutations (32)(33)(34)(35)(36)(37)(38)(39)(40). While KRAS amplification has also recently been reported at acquired MET TKI resistance in METex14-mutated NSCLC (10), the broader role of compensatory genomic events providing signaling pathway re-activation remains less well-understood in METex14mutated NSCLC.…”
Section: Discussionmentioning
confidence: 99%